Compliance with family nursing and the impact of nurse-led interventions during acute care : family members' and nurses' perspectives - Kiwanuka, Frank (Publications of the University of Eastern Finland, ISSN 1798-5706, 2023)
Perhehoitotyön käytäntöjen ja hoitajavetoisten interventioiden vaikutus akuuttihoidon aikana : perheenjäsenten ja hoitajien näkökulmat.
Keywords: Family Nursing; Critical Care Nursing; Critical Care; perhehoitotyö; tehohoito; hoitotiede; familjevårdsarbete; intensivvård; vårdvetenskap; Uganda; family-centered care; family healthcare; nursing science